PEMANFAATAN CITRA SPOT 5 DAN SISTEM INFORMASI GEOGRAFIS UNTUK KAJIAN KESESUAIAN LAHAN TAMBAK UDANG BERBASIS KARAKTERISTIK BIOFISIK LAHAN Kasus: Kabupaten Bombana, Provinsi Sulawesi Tenggara - , SAWALUDIN,S.Pi, Prof. Dr. Totok Gunawan, M.S ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research was conducted by utilizing SPOT 5 image (Systeme de I'Observation Probatoire de la Terre) and Geographic Information System to asses the suitability of shrimp farm biophysical characteristics of land in Bombana Regency, Southeast Sulawesi Province. The main purpose of research is to know the ability of SPOT 5 image to extract parameters of shrimp farm suitability, assess the land suitability of shrimp farm biophysical characteristics with the use of geographic information systems (GIS), and recommended direction of the land use function based management of shrimp farm. The way of research was conducted with image processing and spatial modeling of Geographic Information Systems. The image processing technique consists of image enhance for interpretation of landforms, maximum likelihood classification for land use interpretation, and image transformation to know the suspended load distribution. The Geographic Information System was utilized to analyze the interpretation results and image transformation and field data using matching arithmethic method by making overlay several maps into biophysical characteristic for land suitability of shrimp farm. The SPOT 5 image has the ability to extract biophysical parameters for land suitability of shrimp farm. The overall accuracies of land use interpretation reaches 89%. This suggests that the ability of SPOT 5 image for land use interpretation and the ability of interpreters in good categories. The results showed that the criteria for shrimp farm in coastal land Bombana Regency appropriate (S1) occupies an area of 6952.52 hectares or 32.79%, according to class rather occupies an area of 3.679.72 hectares or 17.35%, and class are not according to occupy an area of 10,574.91 hectares or 49.86% from the research area. The recommended land use direction is area of shrimp farm cultivation that takes into account the sustainability aspects of aquaculture and not make changes for the built land.